Desarrollo de un sistema de gestión energética en conformidad con la norma iso 50001:2018 para seyquiin cia. Ltda., en el año 2022. - Reyes Segovia, Iván Geovanny (2023)
This research work was carried out at Seyquiin Cia. Ltda. located in the city of Ambato, being a chemical products production company for the textile sector, it needs an adequate optimization and efficient uses of energy taking into account that the demand It is in a growth trend causing customers to be increasingly demanding looking for suppliers that comply with management systems and are committed to continuous improvement, it is for this reason that the objective of the work is to develop an energy management system based on the ISO 50001:2018 standard in order to establish an adequate administration of energy resources and the best use of them, you will obtain opportunities to enter new markets, satisfying customers. To verify the current state of the company, an initial audit of the requirements established by the ISO 50001: 2018 standard was carried out, in which it was evidenced that the company has 6,071% of total compliance, identifying opportunities for improvement in administrative processes. and productive.